2021
DOI: 10.1162/jocn_a_01653
|View full text |Cite
|
Sign up to set email alerts
|

An Important Step toward Understanding the Role of Body-based Cues on Human Spatial Memory for Large-Scale Environments

Abstract: Moving our body through space is fundamental to human navigation; however, technical and physical limitations have hindered our ability to study the role of these body-based cues experimentally. We recently designed an experiment using novel immersive virtual-reality technology, which allowed us to tightly control the availability of body-based cues to determine how these cues influence human spatial memory [Huffman, D. J., & Ekstrom, A. D. A modality-independent network underlies the retrieval of large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…They concluded that visual information might play a key role in large-scale spaces compared to bodily cues. These findings are raising an important debate [1,42] concerning how and when bodily cues influence spatial memory. Their contribution might depend on the type of the task (i.e., egocentric or allocentric), the spatial scale (i.e., peripersonal and large scale), and the type of the interface (linear vs. exponential ability to use virtual and real-world bodily cues).…”
Section: Virtual Bodily Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that visual information might play a key role in large-scale spaces compared to bodily cues. These findings are raising an important debate [1,42] concerning how and when bodily cues influence spatial memory. Their contribution might depend on the type of the task (i.e., egocentric or allocentric), the spatial scale (i.e., peripersonal and large scale), and the type of the interface (linear vs. exponential ability to use virtual and real-world bodily cues).…”
Section: Virtual Bodily Representationmentioning
confidence: 99%
“…Their contribution might depend on the type of the task (i.e., egocentric or allocentric), the spatial scale (i.e., peripersonal and large scale), and the type of the interface (linear vs. exponential ability to use virtual and real-world bodily cues). It might be that bodily cues are particularly relevant for egocentric and near-space representation of the environment also depending on the role of the VR interface [42] or that the ability to use cues follows an exponential trend in real-world compared to VR navigation [1].…”
Section: Virtual Bodily Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, spatial navigation, in addition to vision, requires the active recruitment of bodily information (e.g., motor commands, proprioception, vestibular system) and cognitive processes (e.g., spatial attention, spatial operations, and route decision-making) (Chrastil and Warren, 2012 ). How these cues influence egocentric and allocentric frames of reference is still a matter of debate (Chrastil and Warren, 2012 ; Huffman and Ekstrom, 2021 ; Steel et al, 2021 ). In particular, some authors (e.g., Huffman and Ekstrom, 2021 ) suggest that egocentric spatial memory is more affected by body-based information or peri-personal space tasks.…”
Section: Introductionmentioning
confidence: 99%
“…How these cues influence egocentric and allocentric frames of reference is still a matter of debate (Chrastil and Warren, 2012 ; Huffman and Ekstrom, 2021 ; Steel et al, 2021 ). In particular, some authors (e.g., Huffman and Ekstrom, 2021 ) suggest that egocentric spatial memory is more affected by body-based information or peri-personal space tasks.…”
Section: Introductionmentioning
confidence: 99%